A Digital Interactive Exhibition from the Inside Out - POP-TIRON, Cristina (Studia Universitatis Babeș-Bolyai Dramatica, 2023)
Performance Review: Human Presence in a Digital World showcase by the Digital Interactive Arts Master Program and the Performing Arts and Film Master Program, Faculty of Theatre and Television, Babeș-Bolyai University. Coordinators: Professor Rodica Mocan and Cristina Pop-Tiron. Central Shopping Center (3 February 2023).